Bismuth Schiff base complex and its oxide nanoparticles as photocatalyst for the removal of dyes from water - Behrouz Shaabani; Shadi Soleimaninia (International Journal of Ceramic Engineering & Science)
Abstract Bismuth oxide and bismuth complexes with organic ligands, particularly Schiff bases, have received much attention due to their non‐toxicity, antibacterial, and photocatalytic properties in removing water and environmental contaminants by oxidative degradation. This work investigates the synthesis of bismuth complexes with the salicylidine Schiff base ligand of H2L through hydrothermal and solvothermal methods, the preparation of bismuth oxide nanoparticles from these complexes, and the synthesis of bismuth oxide nanoparticles from bismuth nitrate. To characterize the products, several techniques including infrared, UV–vis, X‐ray diffraction (XRD), energy‐dispersive X‐ray analysis, and scanning electron microscopy (SEM) have been used. Hydrothermally and solvothermally produced bismuth(III) complexes with H2L had particle sizes of about 46 and 15 nm, respectively, while oxide nanoparticles made from them had sizes of about 42 and 52 nm, respectively. The study also investigates the usage of complexes and oxide nanoparticles as photocatalysts under an ultraviolet (UV) lamp (30 W) irradiation to remove contaminants such as methyl orange, acid red 14, orange acid 7, and malachite green from water. The results showed that the bismuth complexes and oxide nanoparticles effectively remove these dyes from contaminated water samples.